Achieving a Zero Central Line-Associated Bloodstream Infection Rate in 4 Critical Care Units in Lebanon. Issue 2 (September 2019) - Jamous, Sabath; Kouatly, Iman; Zaatari, Rafika; Kurdahi Badr, Lina
Abstract : Every health care facility aims to achieve and maintain a zero central line-associated bloodstream infection (CLABSI) rate. Infections can be costly for institutions of any size and are often not covered by health insurance. The interventions put in place in this quality improvement project were implemented in 4 phases: (1) develop a new standard of care for central lines and give nurses full responsibility for the care and handling of these lines (including blood sampling); (2) revise policy and provide educational sessions to support nurses; (3) document compliance with the new policy; and (4) document CLABSI rates. The project took place during a 15-month period between January 1, 2016 and March 30, 2017, in 4 critical care units in a university medical center in Lebanon. The results revealed a reduction in CLABSI rates from a maximum rate of more than 17 per 1000 catheter days to zero per 1000 catheter days, which was sustained for 10 months. Nurse compliance with the new policy after 3 months ranged from 95% to 99%.